Mobile Application: A Serious Game Based in Gamification for Learning Mathematics in High School Students - Ortiz, Willington (2022)
In the present study, a serious game based on gamification techniques was developed to motivate the learning of mathematical topics seen in the last academic grade of Peruvian high schools. The proposed game was developed for mobile devices and uses a cloud-based web infrastructure. In addition, gamification techniques such as avatar, levels, progress indicators and rewards were used for its design. A total of 14 students participated in the experiment and qualitative data were collected through a questionnaire. The results showed that the selected gamification techniques were very effective in motivating learning, the serious game had a good user experience, and the students were satisfied with the learning experience of the game.